2010
DOI: 10.1007/s10450-010-9212-7
|View full text |Cite
|
Sign up to set email alerts
|

The separation of GMP from milk whey using the modified chitosan beads

Abstract: The cationic property of chitosan was used to adsorb glycomacropeptide (GMP) molecules from milk whey proteins. β-cyclodextrin was immobilized to native chitosan beads by cross-linking with 1,6-hexamethylene diisocyanate (HMDI). The resultant modified beads (CS-HMDI-BCD) presented superior adsorption affinity and capacity towards GMP. At pH 3.0, 90.23% of GMP was adsorbed with a maximum adsorption capacity corresponding to 12.87 mg of sialic acid/g-adsorbent. Desorption experiments showed that the modified bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…The MIP MAA were found largely macroporous, with the BET specific surface area and pore volume of ~70 m 2 /g, and 0.31 cm 3 /g, respectively. It has been demonstrated in many studies that the adsorption mechanisms on such macroporous polymeric adsorbents are predominantly chemical adsorption in nature, of which the surface area and pore size offer little insightful information. For example, the MIP synthesized by Zhu et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MIP MAA were found largely macroporous, with the BET specific surface area and pore volume of ~70 m 2 /g, and 0.31 cm 3 /g, respectively. It has been demonstrated in many studies that the adsorption mechanisms on such macroporous polymeric adsorbents are predominantly chemical adsorption in nature, of which the surface area and pore size offer little insightful information. For example, the MIP synthesized by Zhu et al .…”
Section: Resultsmentioning
confidence: 99%
“…possessed a surface area of ~200 m 2 /g, which is less than the related are of NIP. The macroporous, polymeric adsorbents for protein separation presented a surface area of less than 50 m 2 /g …”
Section: Resultsmentioning
confidence: 99%
“…For example, Zhu et al found the surface area of a MIP in the range of ∼200 m 2 ·g –1 , but the related NIP presented a higher surface area than the MIP. Xu et al synthesized chitosan-based adsorbents for adsorption of dyes in aqueous solution with the surface area of ∼50 m 2 ·g –1 , The cross-linked chitosan–cyclodextrin adsorbents for the purification of whey proteins presented a surface area of ∼45 m 2 ·g –1 …”
Section: Resuts and Discussionmentioning
confidence: 99%
“…Nakano et al (2004) reported use of epichlorohydrin-treated chitosan resin to separate GMP from whey. Li et al (2010) prepared β-cyclodextrin immobilized chitosan beads cross-linked with 1, 6-hexamethylene diisocyanate for isolation of GMP from whey. These adsorbents are not suitable for production of food grade GMP as they are prepared using toxic chemicals.…”
mentioning
confidence: 99%